A study on comprehensive anti-calcification treatment technology for bioprosthetic valves - Yongkai Zhang; Yumiao Wang; Jie Hao; Haiyang Wei; Yana Meng; Xinwei Yang; Shengshou Hu; Jianye Zhou (Journal of Materials Science: Materials in Engineering)
Abstract Background Calcification is the primary cause of bioprosthetic material degradation, triggered by various factors. Although many studies have proposed different anti-calcification methods, most of them focus on a single target and modify it, while the treated tissue is still stored in glutaraldehyde, re-exposing them to calcification-prone environments, thus failing to achieve ideal clinical application. Methods Decellularization was performed using surfactants Triton X-100, sodium dodecyl sulfate (SDS), and sodium deoxycholate (SDC) to remove cellular membrane phospholipid fragments. Sodium bisulfite (SBS) was then used to neutralize unbound aldehyde groups. Finally, the treated tissue was stored in a 75% glycerol solution. A series of biomechanical properties of the treated bovine pericardium were evaluated in vitro, and its anti-calcification properties were assessed through a 6-month in vivo implantation study using a sheep model. Results Compared with the glutaraldehyde-treated control group, the tissues treated with the new comprehensive anti-calcification method showed no significant changes in tensile strength or elongation at break. Additionally, no adverse effects on coagulation or hemolysis were observed, and the use of surfactants showed no significant cytotoxicity. Subcutaneous implantation in rats and mitral valve implantation in sheep model showed significantly improved anti-calcification performance compared to the glutaraldehyde control group. Conclusion This study proposes a comprehensive anti-calcification treatment method, which includes removing cellular debris, reducing phospholipids, neutralizing residual aldehyde groups, and storing the tissue in glycerol. This approach offered a new avenue for further research in the field and significant potential for clinical application.